Neural networks in the framework of granular computing - Pedrycz, Witold (1953- ) (Zielona Góra: Uniwersytet Zielonogórski)
The study is concerned with the fundamentals of granular computing and its application to neural networks. Granular computing, as the name itself stipulates, deals with representing information in the form of some aggregates (embracing a number of individual entitites) and their ensuing processing. We elaborate on the rationale behind granular computing.
Keywords: information granulation; pyramid architectures; encoding and decoding; neural networks; learning; knowledge representation